2020
DOI: 10.3847/1538-4357/ab88b3
|View full text |Cite
|
Sign up to set email alerts
|

Digging for Relics of the Past: The Ancient and Obscured Bulge Globular Cluster NGC 6256

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 70 publications
2
24
0
Order By: Relevance
“…Figure 9 shows the age-metallicity distribution for the bulge GCs with available age estimate, where NGC 6440 is marked as a large red square. The data for the other clusters are mainly from Saracino et al (2019, see their Figure 16) and Oliveira et al (2020, see their Figure 12) with the addition of the recent age determination of NGC 6256 (Cadelano et al 2020). We also mark the age-metallicity of the oldest stellar population in the two Bulge Fossil Fragments (BFF; namely Terzan5 and Liller1) so far discovered into the bulge (Ferraro et al 2009b(Ferraro et al , 2016b(Ferraro et al , 2021.…”
Section: Discussionmentioning
confidence: 97%
“…Figure 9 shows the age-metallicity distribution for the bulge GCs with available age estimate, where NGC 6440 is marked as a large red square. The data for the other clusters are mainly from Saracino et al (2019, see their Figure 16) and Oliveira et al (2020, see their Figure 12) with the addition of the recent age determination of NGC 6256 (Cadelano et al 2020). We also mark the age-metallicity of the oldest stellar population in the two Bulge Fossil Fragments (BFF; namely Terzan5 and Liller1) so far discovered into the bulge (Ferraro et al 2009b(Ferraro et al , 2016b(Ferraro et al , 2021.…”
Section: Discussionmentioning
confidence: 97%
“…Comparing the ages we measure with those in the literature, there are only two clusters with extant age measurements: For NGC 6256, an isochrone-fitting analysis of photometry from the first-epoch HST imaging was recently presented by Cadelano et al (2020), who found an age of 13.0±0.6 using presumably identical Victoria-Regina isochrones but a different (maximum likelihood) fitting technique, in excellent agreement with our age of 12.9±1.0 Gyr (Table 3). Meanwhile, NGC 6342 is included in the relative age study by De Angeli et al (2005), who find a young relative age, consistent with our results.…”
Section: The Age-metallicity Relationmentioning
confidence: 95%
“…As an additional complication, distances from literature compilations, used to calculate orbital properties, can be unreliable as well, placing clusters on the wrong side of the Galactic bulge in some cases (e.g. Alonso-García et al 2015;Cadelano et al 2020). In addition, we know that not all MWGCs presently located in the inner Milky Way are confined to the Galactic bulge, instead showing a kinematic diversity including interlopers from the halo and thick disk (Ortolani et al 2019;Cadelano et al 2020;Pérez-Villegas et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a dense cluster (log ρ 0 ≈ 5.9 in units of M pc −3 ; Baumgardt & Hilker 2018) located in the Galactic bulge, at a distance of 6.8 kpc from the Sun (Cadelano et al 2020b) and characterized by a relatively low metal content compared to typical bulge GCs ([Fe/H]= −1.6; Vásquez et al 2018). In Cadelano et al (2020b), we applied a well-tested procedure (see Pallanca et al 2019Pallanca et al , 2021 to quantify the differential reddening affecting the cluster and we derived a high-resolution exctiction map (see Figure 3 in Cadelano et al 2020b): color excess variations as large as δE(B − V ) ∼ 0.51 mag were measured in the relatively small 160 × 160 field of view (FOV) sampled by the adopted data-set. The differential reddening corrected CMD allowed the authors to derive an age of 13 ± 0.5 Gyr.…”
Section: Introductionmentioning
confidence: 99%